Implementasi Marketing Mix dalam Perbankan Syariah - Siska Anggie Melani (Sahmiyya, 2022)
The sharia marketing mix is ​​based on an Islamic perspective, namely marketing that prioritizes the values ​​of justice and honesty and adheres to the Qur'an and authentic hadith. The use of the marketing mix in the banking world is carried out using concepts that are in accordance with the needs of the bank. The marketing mix is ​​an integrated marketing activity. Each element cannot run independently without the support of other elements. The elements in the marketing mix are product, price, location and promotion.